Development communication in a different key - Moran, Antonio G. (UP Los Baños Journal, 1993)
Development communication has been used as a term to refer to the systematic use of communication strategies and techniques for steering macro-and micro scale development efforts of agricultural and industrializing countries toward human betterment. The paper recontrues the dominant view of development communication as a conveyor of knowledge and technology. This article assays to look at development communication's potential as a structuring process to help anticipate and preempt the imposition of counter-development knowledge and interests. Using personal construct theory as an exempler of constructivism, the paper fuses this paradigm with critical theory and outlines a dibetic-heuristic approach to help clarify historically, situationally and intersubjectively relevant structures, processes and resources. Kelly's constructive alternativism is differentiated from conceptualism and is developed as a dichotomous key for typologizing and analytical-framework building.